2012
DOI: 10.3109/09638288.2012.694573
|View full text |Cite
|
Sign up to set email alerts
|

The use of the comprehensive International Classification of Functioning, Disability and Health core set for stroke for chronic outpatients in three Brazilian rehabilitation facilities

Abstract: The comprehensive ICF core sets for stroke can be used by multidisciplinary teams to classify the life experience of stroke survivors, although efforts to enable and enhance reproducibility are needed to warrant its reliable routine use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 24 publications
0
14
1
4
Order By: Relevance
“…In contrast to previous studies, the categories for chapter (2) Natural environment and chapter (4) Attitudes were absent [8,14] and this may reflect the different method used in this study.…”
Section: Environmental Factor Categoriescontrasting
confidence: 41%
See 3 more Smart Citations
“…In contrast to previous studies, the categories for chapter (2) Natural environment and chapter (4) Attitudes were absent [8,14] and this may reflect the different method used in this study.…”
Section: Environmental Factor Categoriescontrasting
confidence: 41%
“…Riberto et al [14] found that 47.5% of patients considered they had problems with d910 community life, and 66.0% with d920 recreation and leisure. This was also found to be of concern for 39 of 99 Swedish people 3 months post stroke [13].…”
Section: Activities and Participationmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings add to the evidence that the Comprehensive ICF Core for stroke addresses frequently reported functioning problems (Vanhook, 2009;Alguren et al, 2010) among individuals with a previous stroke across different countries and settings (Glassel et al, 2012;Paanalahti et al, 2013;Riberto et al, 2013). Meaningful concepts that could not be linked to ICF categories were classified as nondefinable mental or physical health, health condition, personal factor, or concepts not covered by the ICF (Cieza et al, 2005).…”
Section: Discussionmentioning
confidence: 69%